PERANCANGAN DESAIN INTERIOR RESTORAN DELAGA BIRU, PORSEA, KABUPATEN TOBASA â SUMATERA UTARA - Damayantie, Irma (Jurnal Pengabdian Masyarakat AbdiMas, 2018)
AbstractPorsea area, Tobasa regency, North Sumatra is an area near Lake Toba which is currently still developed its tourism industry. One of the supporters of the tourism industry is in the restaurant business sector. A well-designed restaurant can be an attraction for visitors by not ruling out the food products it sells. Visitors to restaurants in the Delaga Biru tourist area can be visitors who live in homestay there and outside visitors who specifically come to this restaurant. The design of the restaurant will look as attractive as a tourism support facility in Porsea area, Tobasa regency. Design method used to arrange a development of facility supporting activity as tourist attraction of tourism. Method of completion data result comes from observation and reference of the work. While the application of data analysis method is using SWOT qualitative analysis to solve the problem of tourism design which supporting facilities in Porsea itself. Application of the concept of restaurant space applied to the segmentation of its natural tourism. As the result, space concept in designing interior of Delaga Biru restaurant theme is "Tropical Nature". This is in accordance with natural attractions in Porsea, Tobasa regency in the tropics area. The concept of space planning from the Delaga Biru restaurant with the theme will be realized in the indoor and outdoor dining areas. This exotic nature is the basis in designing interior restaurant Delaga Biru.Â Keywords: restaurant design, porsea, tourismÂ AbstrakKawasan Porsea, Kabupaten Tobasa, Sumatera Utara merupakan kawasan di dekat Danau Toba yang saat ini masih dikembangkan industri pariwisatanya. Salah satu pendukung industri pariwisata adalah pada sektor bisnis restoran. Restoran yang didesain dengan baik dapat menjadi daya tarik bagi pengunjung dengan tidak mengesampingkan produk makanan yang dijualnya. Pengunjung restoran pada kawasan wisata Delaga Biru ini dapat merupakan pengunjung yang tinggal pada homestay di sana maupun pengunjung luar yang khusus datang ke restoran ini. Desain restoran akan ditampilkan semenarik mungkin sebagai fasilitas penunjang pariwisata di kawasan Porsea, Kabupaten Tobasa. Metode perancangan digunakan untuk merancang sebuah pengembangan fasilitas penunjang aktivitas sebagai daya tarik pengunjung pariwisata. Metode pengumpulan data diperoleh dari hasil observasi dan acuan karya. Sedangkan penerapan metode analisis data menggunakan analisis kualitatif SWOT untuk memecahkan masalah perancangan fasilitas penunjang pariwisata di Porsea itu sendiri. Penerapan konsep ruang restoran yang diterapkan berfokus pada segmentasi pariwisata alamnya. Kesimpulannya, konsep ruang dalam perancangan desain interior restoran Delaga Biru yakni bertema âTropical Natureâ. Hal ini sesuai dengan wisata alam yang terdapat di Porsea, Kabupaten Tobasa pada daerah tropis. Konsep ruang dari restoran Delaga Biru dengan tema tersebut akan diwujudkan pada area makan indoor dan outdoor. Wisata alam yang eksotis inilah yang menjadi dasar dalam perancangan desain interior restoran Delaga Biru.Â Kata kunci: perancangan restoran, porsea, pariwisata